Technologies for sustainable development - Alka Mahajan; Parul patel; Priyanka Sharma; Proceedings of the 7th Nirma University International Conference on Engineering (7th : NUiCONE 2019 November : 21-22 : Ahmedabad) (Chennai : CRC Press, 2020)
This volume contains a selection of papers presented at the 7th Nirma University International Conference on Engineering NUiCONE 2019'. This conference followed the successful organization of four national conferences and six international conferences in previous years.
Includes index.
Keywords: Engineering; Technological innovations